2015
DOI: 10.1108/cg-01-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity in the governance of the Nigerian securities market

Abstract: Purpose – The purpose of the paper is to identify the key determinants of stock market performance in Nigeria. More specifically, it is an attempt to determine the effect of gender diversity in leadership roles on the performance of the stock market in Nigeria. Design/methodology/approach – The paper uses annual data from 1980 through 2011 to model the development and performance of the Nigerian stock market through a modified Calderon-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Again, female participation in top management promotes the growth performance of SMEs and there is significant inverted U-shaped relationship (Wu et al, 2017). Gender diversity is noted as an important determinant of stock market performance in the Nigerian stock market (Ayadi et al, 2015). They noted that the appointment of females in the management of the Nigerian stock exchange is associated with better performance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Again, female participation in top management promotes the growth performance of SMEs and there is significant inverted U-shaped relationship (Wu et al, 2017). Gender diversity is noted as an important determinant of stock market performance in the Nigerian stock market (Ayadi et al, 2015). They noted that the appointment of females in the management of the Nigerian stock exchange is associated with better performance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Some of the Western economies require a mandatory quota of female on board, while others have provided soft recommendations. Increasing female participation is considered to enhance the corporate decisions and governance quality (Ayadi et al , 2015; Adams and Ferreira, 2009; Green and Homroy, 2018).…”
Section: Institutional Background and Hypotheses Developmentmentioning
confidence: 99%
“…There are mixed theoretical propositions on the impact of board diversity on firm performance: those who argue for more diversity in boardrooms and those who are in favour of corporate monoculture and boardroom uniformity. Some studies found positive links between increased board diversity and firm value (Ayadi et al, 2015;Julizaerma and Sori, 2012;Kim et al, 2013;Lü ckerath-Rovers, 2013;Nielsen and Nielsen, 2013;Taljaard et al, 2015;Zhang, 2012), and others found no relationship (Jhunjhunwala and Mishra, 2012;Mahadeo et al, 2012). Moreover, others indicated that increased levels of diversity could be detrimental to firm value (Akpan and Amran, 2014;Carter et al, 2010).…”
Section: Board Gender Diversitymentioning
confidence: 99%